Using the pimeloyl-CoA synthetase adenylation fold to synthesize fatty acid thioesters - Wang, M; Moynié, L; Harrison, P; Kelly, V; Piper, A; Naismith, J; Campopiano, D (Springer Nature, 2017)
Biotin is an essential vitamin in plants and mammals, functioning as the carbon dioxide carrier within central lipid metabolism. Bacterial pimeloyl-CoA synthetase (BioW) acts as a highly specific substrate-selection gate, ensuring the integrity of the carbon chain in biotin synthesis. BioW catalyzes the condensation of pimelic acid (C7 dicarboxylic acid) with CoASH in an ATP-dependent manner to form pimeloyl-CoA, the first dedicated biotin building block. Multiple structures of Bacillus subtilis BioW together capture all three substrates, as well as the intermediate pimeloyl-adenylate and product pyrophosphate (PPi), indicating that the enzyme uses an internal ruler to select the correct dicarboxylic acid substrate. Both the catalytic mechanism and the surprising stability of the adenylate intermediate were rationalized through site-directed mutagenesis. Building on this understanding, BioW was engineered to synthesize high-value heptanoyl (C7) and octanoyl (C8) monocarboxylic acid-CoA and C8 dicarboxylic-CoA products, highlighting the enzyme's synthetic potential.